2017
DOI: 10.1016/j.energy.2017.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catalyst agglomerate shape in polymer electrolyte fuel cells investigated by a multi-scale modelling framework

Abstract: A multi-scale modelling framework is developed for the PEFC cathode electrode. Unlike the conventional agglomerate model, the effects of the microstructure of the agglomerate are numerically coupled to the fuel cell-scale model in this framework. This is performed through solving the agglomerate-scale model first and subsequently extracting and using the data required to generate the performance curves in the fuel cell-scale model. This enables one to freely investigate the structure of the agglomerate without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Additional assumptions are employed in this study in order to take into account the microstructure of the catalyst layers [10,28,39]:…”
Section: Mathematical Model Developmentmentioning
confidence: 99%
“…Additional assumptions are employed in this study in order to take into account the microstructure of the catalyst layers [10,28,39]:…”
Section: Mathematical Model Developmentmentioning
confidence: 99%
“…The three-dimensional solid, liquid, and gas phases were represented as homogeneous, one-dimensional continuums with volume-averaged values for key properties (e.g., porosity, tortuosity, active surface area, and water saturation). Mass transfer was modeled in the through-plane direction because previous reports have shown that the flow channel and porous CL of flow electrolyzers promote relatively uniform mixing in the in-plane direction. , The governing equations (based on mass, momentum, and charge conservation) were solved simultaneously to quantify the steady-state concentrations of liquid species (H + , OH – , K + , CO 2 , HCO 3 – , and CO 3 2– ), gas species (CO 2 , CO, and N 2 ) as well as the rates of the CO2RR (eq ), the HER (eq ), and acid–base reactions (eqs , , , and ). The boundary conditions are summarized in Figure b.…”
mentioning
confidence: 99%
“…most inuential parameter. Ismail et al 26 studied the inuence of the shape of agglomerates and found that slight changes in structure can substantially improve fuel cell performance. Carbon corrosion models focus on reactions and its inuencing factors and the strategy for mitigating corrosion, while agglomerate models provide ways to calculate performance.…”
Section: Reaction Equationsmentioning
confidence: 99%
“…Among them, the agglomerate model, which shows the best match with experimental data, 22 has been used more oen to study the related issues of CL in recent years. [23][24][25][26] Moein-Jahromi et al 21 used the agglomerate model to simulate the CL, and the results were compared with those of the homogeneous one. A set of parametric studies were performed, in which the agglomerate size was found to be the Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation